2011
DOI: 10.1021/ol2026069
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of a Simple Dithienylethene via Palladium-Catalyzed Regioselective Direct Arylation

Abstract: The direct arylation on the thienyl groups of a diarylethene with various aryl iodides efficiently provided arylated dithienylethenes under palladium catalysis. Unsymmetrically substituted dithienylethenes were also synthesized by this protocol. This procedure allows a rapid access to a variety of aryl-substituted dithienylethenes from a single substrate of a simple dithienylethene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 37 publications
0
48
0
1
Order By: Relevance
“…of aryl iodides different from those used for the selective monoarylation of compound 143. [105] Itami, Shinokubo and co-workers also demonstrated that the site selectivity of the monoarylation of compound 143 was controlled by the proper choice of the palladium ligand. In fact, they found that 143 underwent b-arylation by treatment with 3 equiv.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 97%
See 3 more Smart Citations
“…of aryl iodides different from those used for the selective monoarylation of compound 143. [105] Itami, Shinokubo and co-workers also demonstrated that the site selectivity of the monoarylation of compound 143 was controlled by the proper choice of the palladium ligand. In fact, they found that 143 underwent b-arylation by treatment with 3 equiv.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 97%
“…[61] Again in 2011, Itami, Shinokubo and co-workers employed a PdCl 2 /2,2'-bipyridyl/Ag 2 CO 3 system for the direct arylation of 1,2-di(2-methylthien-3-yl)perfluorocyclopentene (143) with aryl iodides. [105] As shown in Scheme 66, the procedure allowed a rapid access to monoarylated dithienylcyclopentenes 144 in modest yields. [105] Compounds 144 were then shown to be useful substrates for the synthesis of unsymmetrically disubstituted 1,2-dithienylcyclopentenes 145 ( Figure 23) by PdCl 2 /2,2'-bipyridyl/Ag 2 CO 3 -catalyzed reaction with 3 equiv.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
See 2 more Smart Citations
“…9 The Shinokubo group and our group applied direct CH arylation methods, including our β-selective arylation, to the functionalization of a simple dithienylethene. 10 Moreover, a synthesis of spirocyclic thiophenes containing various functional groups, which are potent ligands for σ 1 receptors, was accomplished by our group and the Wünsch group using Pd catalysis as shown in Scheme 3.…”
Section: Regioselective Ch Arylation Of Thiophenes Thiazoles and Pymentioning
confidence: 99%